The Embedded Information Acquisition System of Forest Resource - Ying Liu; Yantao Zhu; Yurong Li; Chao Ni (Institute of Advanced Engineering and Science, 2012)
Forest resource is the material basis of forestry production and forestry sustainable development. Mastering the basic status of forest resource provides effective basis for forest resource’s scientific management. Nowadays the concept of “Digital Forestry” is put forward and 3S technology is used in forestry. Therefore the embedded system of forest resource information acquisition has been designed which integrated embedded technology with GIS, 3G wireless communication technology and GPS. After analyzing the requirement of forestry resource, the overall structure has been established and the system has been developed by using the advanced demo-board OMAP3530.There are six functions including system login, data acquisition, data manage, map operation, GPS positioning and navigation, temperature and humidity measuring to enhance working efficiency, reduce power consumption and get real-time data. On the building Qt/Embedded platform, the upper application program interface is designed. Linux system and applications are successful transplanted. Adopting GPS technology, real-time positioning, navigation and latitude and longitude display functions are achieved. At the same time, the collected small class survey data and temperature and humidity data can be saved; the data can be uploaded and downloaded by using 3G module from internet. The embedded system of forest resource information acquisition has been verified in Lianyungang Xinpu district forest of China, which gives a good guide to forestry management. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1662